Improving Photocatalytic Efficiency with Titanium Dioxide Quantum Dots - Dao, Nam Duy; Lam, Tho Thi; Van, Anh Dieu; Vu, Ha Thi Thu; Trung, Hai Huynh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Titanium dioxide quantum dots (TiO2-QDs), synthesized using a microwave-assisted method, represent a significant advancement in photocatalysis, particularly in the treatment of environmental pollutants. This study focuses on TiO2-QDs synthesized at 200°C for a duration of 5 minutes, using titanium butoxide as a precursor. Characterization through TEM, XRD, PL, and UV-Vis-DRS analyses revealed uniform quantum dots with an average size of 5.28 nm, a bandgap energy of 3.22 eV, and a crystalline anatase phase, indicative of high photocatalytic activity. Notably, these TiO2-QDs demonstrated exceptional performance in degrading methylene blue (MB) in water, achieving a remarkable treatment efficiency of 97.6% in 120 min, significantly outperforming both conventional titanium dioxide nanoparticles and commercial titanium dioxide materials. The reaction conditions were evaluated based on factors such as catalyst dose, initial MB concentration, and pH. The results indicate that optimal degradation efficiency of MB was achieved at a pH of 7, with a catalyst dose of 0.15 g/L and at a low MB concentration. The efficiency slightly decreased to 94.5% after five reuse cycles, emphasizing its significant reusability and stability. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).